A Review on The Professional Development of Elementary Education Teachers in China - Ying Luo; Wenbin Xu (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
The school field is the main field of teachers' study and work, which creates the field space for teachers' professional development. In order to explore the situation of teacher professional development in school field,based on the general condition of the research, from the research scope, the research perspective, the fit between